Plasminogen Activator Inhibitor-1 Expression in Human Liver and Healthy or Atherosclerotic Vessel Walls - Chomiki, N; Henry, M; Alessi, M C; Anfosso, F; Juhan-Vague, I (Thrombosis and Haemostasis, 1994)
Individuals with elevated levels of plasminogen activator inhibitor type 1 are at risk of developing atherosclerosis. The mechanisms leading to increased plasma PAI-1 concentrations are not well understood. The link observed between increased PAI-1 levels and insulin resistance has lead workers to investigate the effects of insulin or triglyceride rich lipoproteins on PAI-1 production by cultured hepatocytes or endothelial cells. However, little is known about the contribution of these cells to PAI-1 production in vivo. We have studied the expression of PAI-1 in human liver sections as well as in vessel walls from different territories, by immunocytochemistry and in situ hybridization.We have observed that normal liver endothelial cells expressed PAI-1 while parenchymal cells did not. However, this fact does not refute the role of parenchymal liver cells in pathological states.In healthy vessels, PAI-1 mRNA and protein were detected primarily at the endothelium from the lumen as well as from the vasa vasorum. In normal arteries, smooth muscle cells were able to produce PAI-1 depending on the territory tested. In deeply altered vessels, PAI-1 expression was observed in neovessels scattering the lesions, in some intimal cells and in smooth muscle cells. Local increase PAI-1 mRNA described in atherosclerotic lesions could be due to the abundant neovascularization present in the lesion as well as a raised expression in smooth muscle cells. The increased PAI-1 in atherosclerosis could lead to fibrin deposit during plaque rupture contributing further to the development and progression of the lesion.